INITIAL DATA ON THE RELIABILITY AND VALIDITY OF THE DEPRESSION,ANXIETY, STRESS SCALE (DEPRESSION, ANXIETY, STRESS SCALE – DASS) - Leontieva, Lora (E-Journal VFU, 2024)
The beginning of a procedure for adaptation of the Depression, Anxiety, StressScale in Bulgarian is presented. Initial psychometric data reveal good reliability and validity.The methodology and the main theoretical concepts in the development of the scale aredescribed. The results of the statistical analysis reveal a good construct and convergentvalidity and excellent internal consistency of both the individual subscales and the entireScale. The T-test for independent samples shows that the scales for depression, anxiety, stressare sensitive to the measured characteristics in clinical and non-clinical samples, with themean values significantly higher in a clinical sample.
Keywords: validity; reliability; adaptation; stress; anxiety; depression; DASS